Peran Gradasi dan Mineralogi dalam Menentukan Kekuatan dan Kompresibilitas Material Disposal Tambang Nikel: Kajian Literatur - Nugraha, Arief Pambudi (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
Mine disposal materials such as tailings, overburden, and waste rocks are critical components in mining operations that require comprehensive understanding of their geotechnical properties to ensure stability and safety of storage facilities. This literature review aims to analyze the role of particle gradation and mineralogical composition in determining shear strength and compressibility of mine disposal materials, with particular focus on nickel mining. A sistematic literature review method was employed by analyzing 30 scientific publications from 2019-2025 obtained from various academic databases. The review findings indicate that particle size distribution (gradation) has significant influence on shear strength and compressibility, where materials with coarser gradation and higher coefficient of uniformity (Cu) exhibit greater shear strength and lower compressibility. Mineralogy, particularly clay mineral content, increases cohesion and microporosity but also increases compressibility under loose conditions. Studies on nickel mine waste demonstrate that ferronickel slag possesses favorable drainage characteristics suitable for rockfill material, while tailings require strict gradation control. In conclusion, comprehensive characterization integrating gradation parameters (Cu, Cc, D50) with mineralogical analysis (XRD, XRF) is essential for predicting mechanical behavior of mine disposal materials and designing safe storage facilities.